Seed germination ecology of feather lovegrass [Eragrostis tenella (L.) Beauv. Ex Roemer and JA Schultes] - Chauhan, Bhagirath S. (Public Library of Science, 2013)
Feather lovegrass [Eragrostis tenella (L.) Beauv. Ex Roemer & J.A. Schultes] is a C4 grass weed that has the ability to grow in both lowland and upland conditions. Experiments were conducted in the laboratory and screenhouse to evaluate the effect of environmental factors on germination, emergence, and growth of this weed species. Germination in the light/dark regime was higher at alternating day/night temperatures of 30/20 °C (98%) than at 35/25 °C (83%) or 25/15 °C (62%). Germination was completely inhibited by darkness. The osmotic potential and sodium chloride concentrations required for 50% inhibition of maximum germination were -0.7 MPa and 76 mM, respectively. The highest seedling emergence (69%) was observed from the seeds sown on the soil surface and no seedlings emerged from seeds buried at depths of 0.5 cm or more. The use of residue as mulches significantly reduced the emergence and biomass of feather lovegrass seedlings. A residue amount of 0.5 t ha-1 was needed to suppress 50% of the maximum seedlings. Because germination was strongly stimulated by light and seedling emergence was the highest for the seeds sown on the soil surface, feather lovegrass is likely to become a problematic weed in zero-till systems. The knowledge gained from this study could help in developing effective and sustainable weed management strategies.